Dasar Pandemi Covid-19 Sebagai Alasan Penerapan Asas No Work No Pay Bagi Pengusaha Untuk Pekerja - Alvian Dharmawan (Faculty of Law, Universitas Airlangga, 2021)
AbstractThe presence of the Covid-19 pandemic has hampered several social activities in life. No exception to the business sector which also effects on the amount of production due to the presence of Covid-19. Companies need to do various ways to avoid termination of employment relationships, which one can be used is by implementing no work no pay to their employees. No work no pay is a principle of wages for workers. To be able to apply these principles, companies must be able to pay attention to several things that become requirements for applying these principles. Therefore no work no pay cannot be used carelessly by employers in terms of providing wages to workers during the Covid-19 pandemic.Keywords: No Work No Pay; ; Pandemic Covid-19; ; Entrepreneur; Labor.AbstrakHadirnya pandemi covid-19 telah menghambat beberapa aktivitas sosial dalam kehidupan. Tak terkecuali sektor usaha yang juga berpengaruh pada suatu jumlah produksi karena kehadiran covid-19. Perusahaan perlu melakukan berbagai cara untuk dapat menghidari adanya pemutusan hubungan kerja, salah satunya yang dapat digunakan yaitu dengan menerapkan no work no pay kepada pekerjanya. No work no pay merupakan suatu asas dalam pengupahan pekerja. Untuk dapat menerapakan asas tersebut, perusahaan harus dapat memperhatikan beberapa hal yang menjadi adanya persyaratan dalam menerapkan asas tersebut. Dengan demikian no work no pay tidak dapat digunakan secara sembarangan oleh pengusaha dalam hal memberikan upah kepada pekerja pada masa pandemi covid-19. Kata Kunci: No Work No Pay; Upah; Pandemi Covid-19; Perusahaan; Pengusaha; Pekerja.